1992
DOI: 10.3109/00365549209054648
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Antibiotic-Induced Lysis of Escherichia coli in vitro is Correlated with Enhancement of LPS Release

Abstract: A kinetic turbidimetric Limulus amebocyte lysate (LAL) assay was used to study the effects of gentamicin, amoxycillin and ciprofloxacin (16 x MIC) upon release of lipopolysaccharide at different stages of a growing Escherichia coli 055:B5:H culture in vitro. In this model a linear correlation was present between the logarithms of colony counts and free LAL activities. Untreated E. coli grew from log values of 4.9 +/- 0.15 (low inoculum) and 6.8 +/- 0.08 cfu/ml (high inoculum) at t = 0 to 8.9 +/- 0.05 and 9.1 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The LPS release from E. coli during a 6 h growth period was 16.8 µg (inoculum size of 10 5 cfu/mL, [235]). The calculated amount of LPS in milk from infected quarters was approximately 10 5 times higher than the highest LPS value observed in blood.…”
Section: Endotoxin Clearancementioning
confidence: 99%
“…The LPS release from E. coli during a 6 h growth period was 16.8 µg (inoculum size of 10 5 cfu/mL, [235]). The calculated amount of LPS in milk from infected quarters was approximately 10 5 times higher than the highest LPS value observed in blood.…”
Section: Endotoxin Clearancementioning
confidence: 99%
“…In meningococci, it was observed that isolates from patients had higher endotoxin-liberating activities than strains isolated from carriers (3). During normal growth, until the stationary phase, most endotoxin remains bound to the cell (4,25,65,69), and a stable ratio of bacterial counts and endotoxin concentration (total and shed) is usually observed (4,25,41,68,78).…”
Section: Endotoxinmentioning
confidence: 99%
“…During treatment of Haemophilus influenzae type b meningitis, peptidoglycans released from the bacterial cell wall into the cerebrospinal fluid (CSF) also contribute to meningeal inflammation (12). Jarisch-Herxheimer reactions that occur during treatment of secondary syphilis were proven not to be mediated by endotoxin (66 (44,79), most of the bacteria were killed within 2 h, whereas endotoxin levels still increased after 6 h. In two studies (52,78), the increase in endotoxin concentrations leveled off after 1 to 2 h, whereas bacterial counts still decreased. In two other studies (9,25), the time course of bacterial killing and endotoxin release occurred in parallel.…”
Section: Endotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…These disease processes have an associated mortality rate of c. 50%, even where appropriate antibiotics are used and intensive care management is A possible explanation for this high mortality is the release of additional endotoxin during antibiotic the rap^.^ Various in-vitro studies have reported release of significant amounts of endotoxin when bacteria are exposed to bactericidal antibiotics. 5- 9 The present study aimed to determine the amount of endotoxin released from bacteria in vitro when exposed to antibioticsduring logarithmic phase growth. The results were correlated with morphological changes in the bacteria following exposure to the antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%